Experimental and Numerical Simulation Studies on the Flow Field Effects of Three Artificial Fish Reefs - Peng Guo; Shuo Zhang; Shishi Zhu; Zhaoyang Jiang (Journal of Marine Science and Engineering)
This paper focuses on three artificial reefs with different functionalities that are to be placed in the marine pasture in South Sulawesi Province, Indonesia, investigating the effects of different incoming current velocities and headward current angles on their flow field effects and aiming to explore the flow field effects of the three reefs and analyze the functionality of their flow fields and flow regimes on the sea area. A combination of PIV experiments and numerical simulation is used to analyze the velocity at the measurement point of the flume, the characteristics of the cross-section flow pattern, and the flow field effects under different incoming velocities and head-on angles, and the accuracy of numerical simulation is verified by flume tests. The results show that the changes in the incoming velocity and the angle of flow on the three reefs have different effects on the volume of upwelling and back eddy; the shape of the reef and the internal structure of the reef do not have any impact on the flow pattern, and the changes in the flow field are different under different conditions. The scale of the flow field reaches optimization under specific conditions.